Unresolved roles of Aux/IAA proteins in auxin responses - Kubalová, Monika; Schmidtová, Martina; Fendrych, Matyáš (Physiologia plantarum, 2025)
Aux/IAA proteins are well-known as key components of the nuclear auxin signaling pathway, repressing gene transcription when present and enabling gene activation upon their degradation. In this review, we explore the additional roles of Aux/IAA proteins in the known auxin perception pathways-the TIR1/AFBs nuclear as well as in the emerging cytoplasmic and apoplastic pathways. We summarize recent advances in understanding the regulation of Aux/IAA protein stability at the post-translational level, a critical factor in auxin-regulated transcriptional output. We further highlight the roles of auxin-nondegradable non-canonical Aux/IAAs in auxin-mediated transcription and their involvement in apoplastic auxin signalling. Additionally, we discuss the importance of Aux/IAAs for the adenylate cyclase activity of TIR1/AFB receptors and speculate on their involvement in the cytoplasmic auxin pathway. Using Arabidopsis root as a model, this work underscores the central role of Aux/IAA proteins in mediating auxin-driven developmental processes and environmental responses. Key questions for future research are proposed to further unravel the dynamic roles of Aux/IAAs in auxin signaling networks.
Keywords: proteiny huseníčku; Arabidopsis; Plant Roots; F-Box Proteins; signální transdukce; regulátory růstu rostlin; Arabidopsis Proteins; kyseliny indoloctové; receptory buněčného povrchu; rostlinné proteiny; Signal Transduction; regulace genové exprese u rostlin; kořeny rostlin; F-box proteiny; Plant Growth Regulators; Indoleacetic Acids; Gene Expression Regulation, Plant; Receptors, Cell Surface; Plant Proteins